RANCANG BANGUN SISTEM E-LEARNING SEBAGAI SARANA PEMBELAJARAN - Sandra J Kuryanti (Universitas Bina Sarana Informatika, 2016)
E-learning is a teaching method that uses electronic media (internet) either formally or informally. Elektronic Learning or better known as E-learning is one of the means used to carry out the teaching and learning process. In the E-learning method using electronic media, especially the Internet as a learning system, as well as the foundation and the logical consequence of the development of information and communication technology. With e-learning students can learn anytime and anywhere without being obstructed time and place, because E-learning provides the flexibility, interactivity, speed, visualization through the various advantages of each medium. In manufacturing method Software Development which is the waterfall model. linear sequential model life or groove classic waterfall model provides a workflow approach to software life or ordered sequential manner starting from the analysis, design, coding, testing and support phases. With e-learning can increase the quantity of interaction between the learning activities of teachers and students, because it is not constrained by a tight time schedule, so that students can make learning anywhere and anytime.